Porous Silicon Refractive Index Measurements with the Assistance of Two types of Lasers - Salih, Saad A. Mohammed (Al-Nahrain Journal for Engineering Sciences, 2017)
Porous Silicon (PSi) samples with (100) orientation n-type were prepared by photo-electrochemical etching process for different variable parameters and fixed electrolyte solution HF:C2H5OH:H2O (2:3:3). Physical and optical properties of PSi would be varied with the variation of process parameters such as current density, anodization time and laser wavelengths. Two types of 50 mW diode lasers were chosen, 473 nm Blue & 532 nm green at 20 mA/cm2 & 15 min etching time to assist the iodization process. The band gap of the fabricated layer has raised up to (2.9 eV) which is more than twice its original value for the c-Si (1.12 eV). _x000D_ Exploiting the obtained gap energy values, the refractive index of porous silicon layer was calculated depending upon Vandamme empirical relation. It was observed that the porosity is modifiable through etching conditions, which in turn makes refractive index also modifiable. Thus, the calculation depended on taking certain parameters as the current density and etching time in order to compare the effect of applying the two laser wavelengths. AFM was applied to observe the homogeneity and roughness of the PSi mono-layer. The results are in a very good agreement with the range of the refractive indices of PSi and the illumination with green laser gives a better conclusion to use in solar cells as a good absorber and a bad reflector.